2008
DOI: 10.1021/jp804797a
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Mechanism Study of UF6 Hydrolysis in the Gas Phase

Abstract: The mechanism of the gas-phase reaction UF 6 + H 2O --> UOF 4 + 2HF is explored using relativistic density functional theory calculations. Initially, H 2O coordinates with UF 6 to form a 1:1 complex UF 6.H 2O. Over an activation energy barrier of about 19 kcal/mol, H 2O transfers a H atom to a nearby ligand F, resulting in UF 5OH + HF. The eliminated HF or another H 2O molecule may form a hydrogen bond with UF 5OH. Starting from UF 5OH, the second HF elimination results in UOF 4. If UF 5OH is in the isolated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 38 publications
3
27
0
Order By: Relevance
“…Previous efforts to characterize this reaction have focused on spectroscopic measurements [5][6][7] and computational studies. [8][9][10][11][12][13] The experimental studies have focused on the spectroscopic detection of uranium species but lacked the temporal resolution to observe the reaction or identify any transient species. Unfortunately, there are major discrepancies between the experimentally observed reaction and computationally predicted mechanisms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous efforts to characterize this reaction have focused on spectroscopic measurements [5][6][7] and computational studies. [8][9][10][11][12][13] The experimental studies have focused on the spectroscopic detection of uranium species but lacked the temporal resolution to observe the reaction or identify any transient species. Unfortunately, there are major discrepancies between the experimentally observed reaction and computationally predicted mechanisms.…”
mentioning
confidence: 99%
“…Unfortunately, there are major discrepancies between the experimentally observed reaction and computationally predicted mechanisms. For example, the computational studies suggest large thermodynamic energy barriers that would likely prevent the reaction of UF 6 and water vapor, [9][10][11][12][13] yet the hydrolysis reaction is known to occur quickly and completely under ambient conditions. [5][6][7] Additionally, one of the long-suspected intermediates of this reaction, UOF 4 , has not been successfully identied under extreme conditions designed to optimize its production such as reacting water with a 5000-fold excess of UF 6 .…”
mentioning
confidence: 99%
“…Recently, Hu et al (2008Hu et al ( , 2009Hu et al ( , 2014 used the relativistic density function theory to computationally show that intermediate species containing a U-O-U bond were found because of several probable reactions involving UF5OH and UF6 or UF5OH and UF5OH under the condition of enriched UF6 and small amounts of H2O (i.e., small ω condition) where ω is the molar ratio of H2O to UF6. In large ω conditions, the coordination energy between UF6 and (H2O)n in UF6-nH2O (e.g., where n = 1-3) increases as water changes from single molecules to the associated dimer and trimer.…”
Section: Pathways To Airborne Uranyl Particlesmentioning
confidence: 99%
“…So far, these molecular dynamics modeling works (Hu et al 2008(Hu et al , 2009(Hu et al , 2014 suggested only the pathway of the UF6 hydrolysis in the gas phase, but none did for the condensed phase in which the formation of UO2F2 aerosol particles exist. The aerosol formation process and kinetics remain unknown.…”
Section: Pathways To Airborne Uranyl Particlesmentioning
confidence: 99%
“…These studies suggested a complex reaction pathway from UF 6 to UOF 4 through a UF 5 OH intermediate, and reported binding energies of formation and vibrational frequencies of molecular fragments [7][8][9]. A subsequent study using DFT with a small-core, scalar relativistic pseudopotential proposed that trimolecular mechanisms are likely involved in formation of the UF 5 OH intermediate [10].…”
Section: *Manuscriptmentioning
confidence: 99%